Konsep Wahdatul Wujud dan Pantheisme : Komparasi Pemikiran Ibn ‘Arabi dan Spinoza Dalam Memahami Keesaan Tuhan - Azrian Isyfaul Fuadi (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This research aims to explain the terms of Pantheism and Wahdatul Wujud historically, so that readers understand how the development of Wahdatul Wujud and Pantheism is often equated, even though the two concepts are raised with different definitions and figures. This paper is a library research with a qualitative method using a data analysis approach related to the figures who discuss and compare two figures, namely, Islamic and Western figures. In general, these two concepts both discuss how the concept of the oneness of God in the view of the creature is explained through philosophical methods, but the clear difference between the two concepts is that Ibn 'Arabi's Wahdatul wujud departs from spiritual experiences that are generally difficult to explain, this can be seen from the history of the development of the spirituality of Sufi scholars such as al-Hallaj and al-Busthami who have first discussed the concept of the oneness of God which became the forerunner of the birth of Wahdatul wujud. However, the advantage of Ibn 'Arabi's concept is the explanation of his theory which is accompanied by a philosophical method that is easier to understand because it involves the ratio (reason). Whereas Spinoza's Pantheism does not involve spiritual experience but purely from the philosophical method explained by Descartes' rationalism method.